HYGIENIC JUSTIFICATION OF RATIONALIZATION OF NUTRITION IN NURSING HOMES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Increasing changes in the body, gradually progressing and eventually leading to the development of senile degeneration, seem inevitable. However, at present, a person is increasingly mastering the knowledge of the regulatory abilities of the body. The development of many human health disorders that previously seemed completely hopeless (for example, atherosclerosis and even cancer) are beginning to be considered as those in which it is possible to look for ways to prevent or even reverse their development. With regard to the aging process, it is extremely tempting to explore the possibilities of a long delay in their onset and progression. [1,5,8,1116,17].